A Novel Spine Fixation System Made Entirely of Carbon-Fiber-Reinforced PEEK Composite: An In Vitro Mechanical Evaluation - Ofir Uri; Yoram Folman; Gil Laufer; Eyal Behrbalk (Advances in Orthopedics)
Background. Semirigid spine fixation systems utilizing nonmetallic materials have emerged as a promising innovation to overcome the inherent disadvantages of metal instrumentation in spine surgery. This study tests the mechanical properties of a novel spine fixation system made entirely of carbon-fiber-reinforced PEEK (CFR-PEEK) composite material (CarboClear System, CarboFix Orthopedics Ltd., Israel). Methods. An in vitro mechanical evaluation of the CFR-PEEK CarboClear system was conducted in compliance with the American Society for Testing and Materials (ASTM) F1717, F2193, and F543 standards. Results. The mean bending yield load, bending ultimate load, and bending stiffness of the construct were 322 N, 363 N, and 45 N/mm, respectively. All tested samples completed 5 × 106 dynamic cycles successfully, with no evidence of fatigue failure at increasing load levels, up to 83% of ultimate bending load. The mean torsional stiffness was 1.0 Nm/deg and the mean screw axial pull-out strength was 2,037 N. Conclusion. The CarboClear Pedicle Screw System has mechanical properties comparable to those of other commonly used titanium-made systems, with superior fatigue properties. The fatigue resistance, modulus of elasticity which is very similar to that of bone, radiolucency, and CT/MRI artifact-free feature of this spine fixation system made entirely of CFR-PEEK may offer advantages over traditional spine fixation systems made of metal alloys.